Rivers in Russian Literature - Ziolkowski, Margaret, 1952- (Book collections on Project MUSE., 2020)
"Rivers in Russian Literature focuses on the Russian literary and folkloric treatment of five rivers-the Dnieper, Volga, Neva, Don, and Angara. Each chapter traces, within a geographical and historical context, the evolution of the literary representation of one river. Imagination may endow a river with aesthetic or spiritual qualities, ethnic, national, or racial associations, or commercial or agricultural symbolism of many kinds. Russian literary responses to these five rivers have much to tell us about the society that produced them as well as the rivers they treat"--